Hubungan Karakteristik Sosial Ekonomi dengan Tingkat Kepuasan Bermukim Pemilik Rumah Sederhana di Perumahan Tamansari Bukit Mutiara Kota Balikpapan - Faridah, Faridah; Manaf, Asnawi (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
The level of satisfaction settled homeowner satisfaction rated based on the condition of the residence and its surroundings are influenced by socio-economic characteristics of residential homeowners. This study was conducted to determine the relationship of socio-economic characteristics with the level of satisfaction in living a simple homeowner in Perumahan Tamansari Bukit Mutiara Balikpapan. The results of the study showed that a simple house is not owned by the people of the lower middle. This is shown on the socioeconomic characteristics of a simple homeowners aged between 35-40 years, S1 educated, worked as private employees with an income of 5 to 7.5 million dollars permonth. Meanwhile, homeowners who are elderly feel less satisfied living in a residential neighborhood because of the lack of activity that involves local people. Simple homeowner satisfaction with their home have been met because the home is already renovation with addition of space that is based on the level of need. Socioeconomic characteristics that influence satisfaction settle the residence include age, education, occupation and number of occupants. Satisfaction simple homeowners against residential neighborhood is met because the residental location of flood -free, guaranteed security and quiet environment. Socioeconomic characteristics that influence satisfaction settled on the environment include residential status, age, education, income and long lived.